2019
DOI: 10.1093/milmed/usz043
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors Associated with Internet Use in Military Medical Students and Residents

Abstract: Introduction Problematic use of video games, social media, and Internet-related activities may be associated with sleep deprivation and poor work performance. The Internet Addiction Test was given to military medical and nursing students and housestaff to assess problematic Internet use. Methods Medical and nursing students at the Uniformed Services University of the Health Sciences and residents from Naval Medical Center San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
7
0
4
Order By: Relevance
“…Dolayısı ile hemşirelik gibi sağlık eğitimi gören öğrenciler teknolojinin bu kadar etkin bir şekilde kullanıldığı bir alan ve zamanda eğitim görmeye başlamıştır 16,22 . Bu da öğrencilerin başta eğitimlerinde kullanacağı bilgi ve araştırmalara ulaşması için internet kullanımını arttırmakta ve sonuçta internet bağımlılığı için riskini artırmaktadır 16,17,22 . Araştırmamızda öğrencilerin İBÖ puan ortalamasına göre normal internet kullanıcısı olduğu ancak %15.5'inde internet bağımlılığı riski olduğu saptanmıştır.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Dolayısı ile hemşirelik gibi sağlık eğitimi gören öğrenciler teknolojinin bu kadar etkin bir şekilde kullanıldığı bir alan ve zamanda eğitim görmeye başlamıştır 16,22 . Bu da öğrencilerin başta eğitimlerinde kullanacağı bilgi ve araştırmalara ulaşması için internet kullanımını arttırmakta ve sonuçta internet bağımlılığı için riskini artırmaktadır 16,17,22 . Araştırmamızda öğrencilerin İBÖ puan ortalamasına göre normal internet kullanıcısı olduğu ancak %15.5'inde internet bağımlılığı riski olduğu saptanmıştır.…”
Section: Discussionunclassified
“…Bu konu ile ilgili yapılan araştırmalarda internet bağımlılığı ile ilgili farklı sonuçlar bulunmaktadır. İnternet bağımlılığı riski ile ilgili yapılan çalışmalarda öğrencilerde %27-67.5 gibi değişen oranlarda internet bağımlılığı olduğu 15,17,20,26,37 ve bağımlılığın orta derecede 22 ya da düşük olduğu belirtmektedir 16 . Çalışmalar arasında farklı oranlar bulunmasının, çalışmalardaki örneklem büyüklüğünün, değerlendirme materyalinin farklı olması, farklı toplumlarda ve farklı zaman aralıklarında yapılmış olmasından kaynaklandığı düşünülmektedir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Ninety-four residents completed an online survey; however, none of the respondents were identified as having moderate internet addiction defined as score on the Internet Addiction Test of ⩾50. In a multivariate regression analysis aiming to identify factors associated with internet addiction, authors found that resident status (vs medical or nursing student status) was associated with score on the Internet Addiction Test independently from other examined lifestyle variables (Schmidt et al, 2019).…”
Section: Individual Studiesmentioning
confidence: 99%